MODELS AND METHODS OF ESTIMATION OF THE PROTECTION OF THE AVIATION SYSTEM - B. I. Bachkalo; V. I. Zolotykh (Научный вестник МГТУ ГА, 2017)
Currently, the security assessment of the primary aviation system from the effects of hazards reduces only the assessment of legality of flight. Such an approach to the assessment of flight safety is not aimed at systemic accounting of the moral and psychological aspects associated with human participation in the aviation system’s management. At the same time, the official statistics showed that the absolute majority of aviation accidents occurred due to the influence of the human factor, most often it was the personal factor of the flight crew. All of the above mentioned determines the necessity of the systemic accounting of the negative manifestations of the aviation specialists’ personal factor, who are involved in the aviation system, primarily they are members of a flight crew. The article substantiates the application of the personal methodological approach to the assessment of the aviation system’s security from the effects of hazardous factors. The features of the application of such an approach are shown in the flight safety assessment model. This model allowed us to develop a methodological apparatus for assessment of the aviation system state. The methodological apparatus is a complex of techniques allowing us to assess the security of a particular flight, taking into consideration the impact of the moral and psychological aspects, which are associated with the personality of a particular pilot, and the state flight safety in aviation formation with the impact of flight crew factor. On the basis of the derived integral indicator, which determines the total amount of threats to the state of the aviation system from the pilot’s personal factor, the methodology for assessment of the flight safety level assurance with the influence of the pilot's personal factor and the methodology for assessment of the flight safety state in aviation formation with the influence of the human factor of the flight crew were developed.